Busy board media as an effort to increase knowledge caries prevention of early childhood - Ariyani, Destika; Noviani, Nita; Widiyastuti, Rini (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Oral and dental health is an important component of Health. Dental caries is common especially in children caused by sweet foods, such as chocolate, candy, and cakes, easily sticking to the teeth. To maintain the health of the teeth and mouth by providing counseling in the form of educational games (APE) such as busy board which provides a variety of activities arranged in one board, aims to keep children engaged and busy in the learning process. Objective: To describe the analysis of busy board media as an effort to increase knowledge of early childhood. Method : is descriptive with a total of 50 respondents using a total sampling. Type of data used is primary data obtained directly by observation using evaluation media busy board pre-test and post-test. The instrument used is busy board and check sheet. Results: The results of the study before the counseling with the evaluation of the busy board is good category as many as 41 ( 82%) respondents, knowledge with sufficient category as many as 8 (16%) respondents, and less knowledge as many as 1 (2%) respondents. After the extension of good category 50 (100%) there is no sufficient category and less (0%). Conclusion: There was an increase in knowledge after being given counseling on food to prevent caries and evaluation with a busy board by 18% and none of the respondents had less knowledge category